PENGEMBANGAN INSTRUMEN PENILAIAN KINERJA SISWA PADA PRAKTIKUM LAJU REAKSI DI SMAN KABUPATEN MEMPAWAH - Romiyah Romiyah; Rachmat Sahputra; Ira Lestari (Universitas Tanjungpura, 2019)
AbstractThis study aimed to determine the level of feasibility and response of chemistry teachers to the performance appraisal instrument of the reaction rate practicum at Mempawah Senior High School. This research took the form of research and development (R & D) which adopted the development model of Borg & Gall. The subject of this study was the student performance appraisal instrument assessed by chemistry teachers at Mempawah Senior High School. The data collection instruments used was the feasibility questionnaire and the chemistry teacher response questionnaire. The results of data processing showed that the student performance appraisal instrument on the reaction rate practicum developed was very feasible (93.33%). The results of the initial trial of the chemistry teacher's response to the product were obtained with a total score of 79.54% with interpretation classified as good. While the main field tests, the teacher's response to the student performance appraisal instrument was obtained with a total score of 81.22% with interpretations classified as very good.Keywords: Chemistry Teacher Response, Feasibility, Reaction Rate, Performance Appraisal,